2018
DOI: 10.1016/j.foodchem.2018.04.130
|View full text |Cite
|
Sign up to set email alerts
|

Addition of mushroom powder to pasta enhances the antioxidant content and modulates the predictive glycaemic response of pasta

Abstract: This study reports the effects of addition of mushroom powder on the nutritional properties, predictive in vitro glycaemic response and antioxidant potential of durum wheat pasta. Addition of the mushroom powder enriched the pasta as a source of protein, and soluble and insoluble dietary fibre compared with durum wheat semolina. Incorporation of mushroom powder significantly decreased the extent of starch degradation and the area under the curve (AUC) of reducing sugars released during digestion, while the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 43 publications
7
87
0
1
Order By: Relevance
“…RF showed relatively lower values for protein, ash and fibre. Similar values for protein, ash and fibre content have been earlier reported for RF (Wanyo et al ., ; Singh et al ., ), MP (Carneiro et al ., ; Lu et al ., ) and CP (Sharma et al ., ; Gull et al ., ). As expected, total phenolic content and antioxidant activity of MP and CP were greatly higher (over ten times more) than that of RP.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…RF showed relatively lower values for protein, ash and fibre. Similar values for protein, ash and fibre content have been earlier reported for RF (Wanyo et al ., ; Singh et al ., ), MP (Carneiro et al ., ; Lu et al ., ) and CP (Sharma et al ., ; Gull et al ., ). As expected, total phenolic content and antioxidant activity of MP and CP were greatly higher (over ten times more) than that of RP.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, the result in this study further confirms that the antioxidant activity of enriched muffins is a factor of constituent bioactive compounds (TPC and TCC). The increase in DPPH upon the addition of carrot pomace and shiitake mushroom has earlier been reported (Ahmad et al ., ; Lu et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Pasta is durum wheat-based inexpensive food product, famous worldwide because of its low cost, versatility, convenience, and excellent shelf life attributes (Desai, Brennan, & Brennan, 2018;Littardi et al, 2019). Although durum wheat semolina is essential for providing the desirable textural and color characteristics during the cooking process (Yadav, Balasubramanian, Kaur, Anand, & Singh, 2012), more recently other grains have been used to partially replace it, offering an improved physical and nutritional qualities (Lu et al, 2018). Most of these additional ingredients has focused on manipulation of glycaemic index (GI) since clinical reports have suggested that food with low GI has been directly associated with the reduced risks of hyperlipidaemia, cardiovascular diseases, extending satiety, and improved insulin sensitivity (Chillo, Ranawana, & Henry, 2011;Dona, Pages, Gilbert, & Kuchel, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these additional ingredients has focused on manipulation of glycaemic index (GI) since clinical reports have suggested that food with low GI has been directly associated with the reduced risks of hyperlipidaemia, cardiovascular diseases, extending satiety, and improved insulin sensitivity (Chillo, Ranawana, & Henry, 2011;Dona, Pages, Gilbert, & Kuchel, 2010). Researchers have developed the pasta with various bioactive ingredients such as pasta from fish material (Desai, Brennan, & Brennan, 2019;Desai et al, 2018;Parvathy, Bindu, & Joshy, 2017), mushroom powder-based pasta (Gao, Brennan, Mason, & Brennan, 2016;Lu et al, 2018), millets pasta (Gull, Prasad, & Kumar, 2015;Jalgaonkar & Jha, 2016;Kamble et al, 2019), cereal, pseudocereal, and super grain-enriched pasta (Benhur et al, 2015;Menga et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cooked noodles were dried by vacuum freezing for 18 h (FD‐2, Beijing, China) and ground into powder by a grinder (IKA M20, Germany). Near infrared spectra of ground samples were determined by a Calorie Answer (CA‐HM, JWP, Japan) based on the method of Lu et al The reflectance mode was used to measure the samples and the cereals‐powdered cereals and dried noodles modes were used for analysis. According to the different vibrational behavior of molecular bonds, mainly CH, OH, and NH, NIRS could rapidly detect the corresponding ingredient in food, including protein, fat, carbohydrate, and water …”
Section: Methodsmentioning
confidence: 99%